Cerebral desaturation during neonatal congenital heart surgery is associated with perioperative brain structure alterations but not with neurodevelopmental outcome at 1 year. (4th April 2022) - De Silvestro, Alexandra A; Krüger, Bernard; Steger, Céline; Feldmann, Maria; Payette, Kelly; Krüger, Julia; Kottke, Raimund; Hagmann, Cornelia; Bosshart, Marco; Bürki, Christoph; Dave, Hitendu; Tuura, Ruth; et al.
Abstract: OBJECTIVES: The significance of intraoperative cerebral desaturation (CD) measured by near-infrared spectroscopy (NIRS) to predict neurological outcome after congenital heart surgery is uncertain. The goal of this study was to compare brain structure changes and neurodevelopmental outcome in patients with severe congenital heart disease with and without intraoperative CD. METHODS: Neonates requiring congenital heart surgery were enrolled in a cohort study. NIRS data from their first cardiac operation were collected. Pre- and postoperative brain magnetic resonance imaging results and Bayley-III scores at 1 year were compared between patients with and without CD, defined by 2 NIRS thresholds: regional cerebral oxygen saturation (rSO2 ) of 45% ( 45%rSO2 ) and rSO2 below 20% of baseline value ( 20%BLrSO2 ). RESULTS: Thirty-two patients (72% male) with d-transposition of the great arteries (n = 24, 75%) and other complex types of congenital heart diseases (n = 8, 25%) were analysed. Perioperative relative lateral ventricle volume change was increased in patients with versus without intraoperative CD ( P = 0.003 for 45%rSO2, P = 0.008 for 20%BLrSO2 ). For 45%rSO2, the effect of CD remained significant after adjusting for age at postoperative scan, time between scans and cardiac diagnosis ( P = 0.019). New intracranial lesions occurred predominantly in CD groups (6/6 patients for 45%rSO2, 5/6 patients for 20%BLrSO2 ). Neurodevelopmental outcome at 1 year was not associated with intraoperative CD. CONCLUSIONS: This study demonstrates the clinical relevance of NIRS monitoring during congenital heart surgery. The occurrence of intraoperative CD is associated with perioperative lateral ventricle volume change and new intracranial lesions. Abstract : Survival of patients with severe congenital heart diseases (CHD) undergoing neonatal cardiopulmonary bypass (CPB) has increased due to advances in surgical and perioperative management.